PENERJEMAHAN RAMAH GENDER - Farida Nur Afifah (Lajnah Pentashihan Mushaf Al-Qur'an, 2021)
This article is motivated by the phenomenon that there is a gender biased translation in the Ministry of Religion’s 2002 translation of the Qur’an which was subsequently revised in 2019. The issue raised is how the method and quality of translation of the verses related to gender in the Al-Qur’an dan Terjemahnya (Qur’an and its translation) in the refinement edition of 2019? This article concludes, first, that the translation method is dominated by communicative translation. This can be seen from the number of translations which are more oriented to the target language recipients, the number of explanations, both brief and detailed, such as explanations in the form of footnotes or explanations in the bracket. Second, the translation is dominated more by semantic and stylistic equivalence levels, thus, it can be said that the translation of gender-related verses has understood and does not contain gender bias. Whereas, in its incompatibility, the cultural level is dominated, because the culture between the recipients of the source language and the target language is different.